Application of organic farming system to conventional rice cultivation at Timpag rice seed farm, Tabanan, Bali - Iqbal Erdiansyah; Achmad Yayan Sokhibul Fattah; Hidayah, Siti Nurul; Hidayatul Rahmawati; Ida Bagus Nyoman Ray Aditya (International Integrated Agricultural Journal (IIAJ), 2025)
Organic farming is a cultivation system that prioritizes using natural and environmentally friendly inputs to create sustainable agriculture. This research/implementation aims to determine the use of liquid organic fertilizer (POC), Jakaba, tofu waste POC, and refugia plants in supporting organic rice cultivation in conventional rice cultivation. Activities were carried out from March to May 2025 at the Timpag Rice Seed Farm, Tabanan, Bali. Jakaba liquid organic fertilizer and tofu waste were applied periodically with the spray method starting at 14 days after planting (HST) with an interval of two weeks until entering the generative phase. Meanwhile, refugia plants such as zinnia, kenikir, and widelia were planted around the cultivation field to support pest biological control. Parameters observed included plant height, number of productive tillers, and insect diversity index. The results showed that the application of POC and refugia can support the growth of rice plants and create a balanced agricultural ecosystem. Thus, the application of organic inputs and ecological approaches like this has great potential in supporting a productive and sustainable organic farming system.